2010
DOI: 10.1590/s0102-311x2010000100021
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação cultural do Chronic Liver Disease Questionnaire (CLDQ) para população brasileira

Abstract: Nesse estudo realizaram-se a tradução para o português e a adaptação cultural do instrumento Chronic Liver Disease Questionnaire (CLDQ) para uso no Brasil. O instrumento foi traduzido da versão original (inglês) para a língua portuguesa pelos autores e, posteriormente, revisado e avaliado quanto ao grau de dificuldade das traduções e equivalência por tradutores bilíngües. O instrumento foi, então, aplicado em 20 pacientes com hepatopatia crônica selecionados aleatoriamente. Não houve dificuldade na compreensão… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 13 publications
0
8
0
8
Order By: Relevance
“…(13) Regarding the MELD assessment of study participants, most patients had a value that was equal to or greater than 15 (77.3%) at the time of the disease. The data showed that patients had more severe disease compared with those in a Brazilian study in which 59% of the transplanted patients had a MELD greater than 15, and 41% had MELD scores less than or equal to 15; (7) another study in London, with 1,032 transplanted adult patients, which measured MELD in the immediate pre-transplant period, found that 45.1% of patients had MELD scores less than 15, 26.7% between 15-25, and 28.2% were higher than 25. (14) The CTP criterion has previously been the most frequently used in the assessment of disease severity.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…(13) Regarding the MELD assessment of study participants, most patients had a value that was equal to or greater than 15 (77.3%) at the time of the disease. The data showed that patients had more severe disease compared with those in a Brazilian study in which 59% of the transplanted patients had a MELD greater than 15, and 41% had MELD scores less than or equal to 15; (7) another study in London, with 1,032 transplanted adult patients, which measured MELD in the immediate pre-transplant period, found that 45.1% of patients had MELD scores less than 15, 26.7% between 15-25, and 28.2% were higher than 25. (14) The CTP criterion has previously been the most frequently used in the assessment of disease severity.…”
Section: Discussionmentioning
confidence: 72%
“…(3) The CTP Classification is based on latest results of liver function laboratory tests, including bilirubin, albumin, prothrombin time, and severity of patient symptoms regarding ascites and degree of hepatic encephalopathy. Results are scored on a scale ranging from 5 to 15 points; they are stratified into class A (5-6), B (7)(8)(9) or C (10)(11)(12)(13)(14)(15), where greater values indicate greater disease severity , providing predictive values of one-to-two year patient survival. (3) Since 2002, the MELD scale has been used by the Organ Procurement and Transplantation Network (OPTN) as a basis for allocation of deceased donor livers for transplantation among adults in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucci et al 13 e Conti et al 14 demonstraram equivalência semântica sem a necessidade de mudanças da versão original. Já outros estudos 15,16 realizaram algumas adaptações metodológicas, assim como no presente estudo.…”
Section: Discussionunclassified
“…Neste estudo, a hepatite B foi a doença hepática mais comum, seguida da hepatite C. Um estudo nacional com pacientes portadores de doença hepática crônica escolhidos aleatoriamente em serviço de transplante de fígado demonstrou prevalência do gênero feminino (65%) com idade média de 48 anos, cujos diagnósticos mais frequentes foram hepatite viral C (25%) e hepatite alcoólica (25%) 19 . A infecção pela hepatite C também foi a doença crônica do fígado mais prevalente em pacientes submetidos à avaliação dermatológica no Paquistão (60%), seguida de hepatite B (28%).…”
Section: Materiais E Métodosunclassified